Mathematical Models of Yield Prediction in Modern VLSI Design - Karapetyan, V. (Mathematical Problems of Computer Science, 2021)
This paper consists of two parts. First the problem of yield in contemporary V LSI manufacturing process is presented. The second part covers the methodology of yield modeling and yield computation technique. The main focus in this paper is put on the random defect limited yield modeling.